A cross-cultural management system: The Ubuntu Company as paradigm. (9th August 2010) - Kroesen, Otto; Rozendaal, Arnoud
Although entrepreneurship is generally considered to be a promising solution for development in Africa, not yet much scientific work is available on the question, how to take the African cultural context in due consideration. A western-style business plan cannot just like that be transferred to the African context. Cultural differences should be taken into account and, moreover, a bridge needs to be built between different value sets. The management model of The Ubuntu Company explicitly takes into account cultural differences and deals with them in a creative way, resulting in a socially responsible business, which is at the same time competitive on the international market. In this management model, African collectivism is taken seriously but counterbalanced by individual initiative and judgement; western style disciplined labour and time management is introduced, but counterbalanced by attention for individual problems and, not the least important, servant leadership of the managers.